THE PERCEPTION OF MTsN MA’RANG STUDENTS ON THE IMPLEMENTATION OF HUMANISTIC APPROACH IN TEACHING WRITING - Syahira Syahira (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2019)
In Indonesia, English as a Foreign Language (EFL) taught in all school levels. So, the effective teaching methods should be employed by the English teachers in achieving the successfulness of EFL teaching and learning process. In order to bring much more benefits for the teachers’ improvement, evaluating teachers’ teaching in the classroom should be conducted. Analyzing the students’ perception becomes one of the ways to use. In hence, the researcher conducted a research that aimed to describe how is the students’ perception about learning activities through humanistic approach in learning writing especially CLL (Community Language Learning) as one method used in applying this approach. This research employed a qualitative experiment research design. A qualitative experiment seeks to produce a description, typically without the use of numbers. It can be subjective in that the results are based on the experimenters’ point of view. Several methods are used in a qualitative experiments; introspection, surveys and questionnaires, and direct observation. These methods mostly involved observation of the user from the researcher. In selecting the participant, the researcher used purposive sampling technique where the participants were choosen based on certain criteria. The purposive sampling technique was used to collect the subjects at MTsN Ma’rang. The data were collected by employing observation and interview. From the data collected, the research found finding. The finding is based on the research objective. There are four learning activities perceived as positive learning activities. They are Group work, Translation, Free Conversation, and Analysis. There are two learning activities perceived as negative learning activities. They are recording and analysis. Key words: students’ perceptions, humanistic approach, learning activities, teaching